The Cycle of the Moon as an Allegory of Modern Dilemma, Despair, and Hope in Shehan Karunatilaka’s novel, “The Seven Moons of Maali Almeida” - Shree Lekha Nandanan (The Bioscan, 2025)
This paper examines the utilisation of lunar imagery and symbolism in Shehan Karunatilaka’s novel “The Seven Moons of Maali Almeida,” which won the Booker Prize in 2022. It analyses the role of the moon as a fundamental motif, symbolising the progression of time, the cycles of life and death, and the protagonist’s exploration of the afterlife. The study examines the historical and cultural importance of the moon in several fields, such as science, religion, and literature, in order to understand its symbolic influence in the novel. Every phase of the moon aligns with significant advancements in Maali’s character progression and the gradual revelation of the mystery behind his demise. The lunar imagery in the context of Sri Lanka’s civil conflict serves as a representation of identity, marginalisation, and the recurring pattern of violence. The research determines that Karunatilaka’s incorporation of moon symbolism enhances the narrative’s exploration of intricate topics such as memory, justice, and the potential for disrupting patterns of violence and injustice.